A Historical and Sociological Study of the Nigerian Air Force (1962 – 1970): Politics, Ethnicism and Army Influence. Issue 4 (2nd October 2022) - Omeni, Akali
ABSTRACT: The Air Force in Nigeria is a compelling subject for sociological enquiry, with an entirely different formative process to the Army. At its inception in 1964, Army officers, not career airmen, commanded the force until 1975. However, whereas the Army cast a long shadow over NAF identity, the Air Force had other institutional pathologies. The "Quota System" of ethnicized recruitment within the military, introduced to balance out ethnic representation, was one such issue. The paper examines how this system, along with the tumultuous politics of 1960s Nigeria, ethnicism and Army influence, shaped the NAF's formative years.